(untitled) (KULT_online, 2010)
Daniel Martin Varisco’s Reading Orientalism is the first monograph to analyse systematically the arguments and theses of Edward Said’s Orientalism. While Varisco acknowledges the importance of Orientalism and seconds some of its main theses, he also accuses Said of being overly polemical and reductionist. Since Varisco himself considers all the major secondary literature and, moreover, much of the vast body of literature on the “Orient” either discussed or ignored by Said, this volume is an extremely valuable contribution to scholarship. Despite some shortcomings of style and theory, Reading Orientalism is indispensable for scholars and students working with Said’s concepts.